The soft refined high-saccharose ration effect on the morphological peculiarities of the gastric mucosa in rats. - Kalinichenko, Yu. A.; Sirotchenko, T. A.; Bobrysheva, A. A. (Морфологія / Morphologia / Morfologìâ, 2012)
Article presents the soft refined high-saccharose ration effect on the morphological peculiarities of the rat’s gastric mucosa. Different areas of fundic part of stomach were materials of the experiment; the animals tagged were at different stages of ontogenesis (late milk period, juvenile and initial reproductive period). Established, that low mechanical stimulation and soft refined high-saccharose ration are formed the morphological peculiarities in rat’s gastric mucosa: fundus glands restriction, muscularis mucosa thinning, diminution of exocrinoсytes (parietal, basic and fossulal, mucocytes) and diminution volumes of nuclei and сytoplasm in experimental animals. Overall the results show the inhibitory effect of the soft refined high-saccharose ration on the gastric secretion with diminution of enzymatic units, decreasing of mucosa functional activity, and forming of chronic diseases.